The Influence Of Capital Structure, Profitability, And Managerial Ownership On Firm Value (Case Study Of Primary Consumer Goods Sector Companies Listed On The Indonesian Stock Exchange For The Period 2018-2022) - Lutfia Damayanti; Deannes Isynuwardhana (Telkom University, 2025)
A company's firm value is determined by the worth of the assets and funds it possesses. Investment risk, corporate performance, and value of an investment may all be assessed using firm value. The goal of this study is to determine how capital structure, profitability, and management ownership affect firm value in enterprises in the main consumer products industry between 2018 and 2022. Firm value is the dependent variable in this study, whereas capital structure, profitability, and management ownership are the independent factors. A purposive sample was used in this study, wherein 17 companies were chosen throughout the course of a 5-year observation period from a total of 33 companies that were listed on the Indonesia Stock Exchange. Panel data regression analysis is the method of data processing used in this study, and the data is tested using Excel 16 and Eviews 12. Descriptive statistics are used in the study. The results of the partial test suggest that, although profitability affects business value, capital structure and management ownership do not. The study's findings are supposed to be used in the company's evaluation in order to maintain or increase profitability and increase investors' desire to invest in the business.